Competency Trend in Human Resource (HR) Development: A Scoping Review - Afandi, Ardian Rahman; Rahmani, Noor Siti; Pontoh, Dyla Jesika; Maulana, Ahmad Ismi; Ari Widianti; Hanna Shakira; Aprilia, Raden Nasya Trifiani (Universitas Islam Indonesia, 2024)
The growing competition among companies is increasing the necessity for management to focus more on a crucial company resource, such as human resources (HR). Competence is recognized as a critical factor in attaining the desired level of performance within the company, as evidenced by past outcomes. However, there has been no study conducted using the systematic literature review (SLR) method to summarize the result in the form of intervention proposed to assist employees. Therefore, this study aimed to determine the trend in competencies required by HR department in a profitable company using SLR, specifically the scoping review method. The result shows that there is a broad overview of the required competencies when managing HR. In this context, competencies related to green human resources (GHR), organizational development (OD), and technology-based development are the most discussed topics.